Exploration of Ethnomedicine for Open Wound Treatment in The Community of Fatumuti Village, Noemuti Subdistrict, North Central Timor - Alim, Anggriani Angela; Muntasir, Muntasir; Purnasari, Cahyani; Regaletha, Tadeus AL. (Jurnal Biologi Tropis, 2026)
Fatumuti Village, Noemuti Subdistrict, North Central Timor Regency, is served by one primary health center covering 12 villages. Most residents work in agriculture, increasing the risk of open wounds and encouraging the continued use of medicinal plants. Although ethnomedicinal studies on wound treatment have been conducted in other regions of Indonesia, this practice has never been scientifically documented in Fatumuti Village.  This study aimed to document the ethnomedicinal practices used by the Fatumuti Village community for treating open wounds, including medicinal plant diversity, plant parts used, and methods of preparation and application. Methods. A qualitative descriptive design with purposive sampling was employed. Data were collected through in-depth interviews, observation, and documentation involving 3 key informants and 27 triangulation informants from March to May 2026. Data were analyzed using the Miles and Huberman interactive model. Nineteen medicinal plant species from 13 families were identified. Leaves were the most frequently used plant part (13 species). Preparation methods included squeezing, pounding, chewing with rice, extracting sap, grating, and oil preparation, while remedies were applied topically one to three times daily, either singly or in combination. This study provides the first scientific documentation of medicinal plants used for open wound treatment in Fatumuti Village and offers baseline data for future pharmacological research and preservation of local ethnomedicinal knowledge.